Functional screening of intracardiac cell transplants using two-photon fluorescence microscopy - Tao, Wen (2012)
Although the adult mammalian myocardium exhibits a limited ability to undergo regenerative growth, its intrinsic renewal rate is insufficient to compensate for myocyte loss during cardiac disease. Transplantation of donor cardiomyocytes or cardiomyogenic stem cells is considered a promising strategy to reconstitute cardiac mass, provided the engrafted cells functionally integrate with host myocardium and actively contribute to its contractile force. We have previously developed a two-photon fluorescence microscopy-based assay that allows in situ screening of donor cell function following their intracardiac delivery. Here we review the techniques and summarize its application for quantitation of the extent to which a variety of donor cell types stably and functionally couple with the recipient myocardium.